Pembuatan kompon cincin karet perapat air minum - Sri Brataningsih Puji Lestari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2007)
The objective of this research was to investigate the effect of ration of natural rubber, synthetic rubber RSS/SBR and carbon black in preparation of compound for Rubber Seal Joint Rings for Water Supply. The ratio of RSS/SBR was 35/63; 25/75; 15/85 phr and Carbon black 20 phr; 30 phr and 40 phr. The vulcanized product of Rubber Seal Joint Rings for Water Supply were then tested their physical properties. Generally the test result were better than those of for Rubber Seal joint rings for Water Supply found in market and they fulfill the requirements of SNI 06-4828-1998 “Spesifikasi cincin karet sambungan air minum, air limbah dan air hujan”. The hardness of product using carbon black in constant quantity and varied quantity of RSS/SBR did not perform significant effect either for pre-ageing. The best hardness of 61 shore A and 65 shore A with 0% change was achieved at the quantity of carbon black 30 phr and 40 phr with ratio RSS/SBR 25/75. The optimum tensile strength of 11.38 MPa and 12.63 MPa with change after ageing of -6.3% and -11.3% was achieved at the quantity of carbon black 20 phr and 30 phr with ratio of RSS/SBR 25/75. The best of elongation at break of 440%with change after ageing 1.35% was achieved at the use of carbon black 20 phr with ratio of RSS/SBR 25/75, where as with ratio RSS/SBR 35/65 and carbon black 30 phr, the elongation at break was 453% and chane after ageing was -1.45%. The best compression set of 5.39% and 5.68% was achieved at the quantity of carbon black 30 phr and 40 phr with ratio RSS/SBR 15/85. The optimum swelling of 2.35% was achieved at the quatity of carbon black and ratio RSS/SBR 25/75 was selected representing the exact composition of vulcanized compound of for Rubber Seal joint rings for Water Supply and perfoming best physical properties fulfilling the quality requirement of SNI 06-4828-1998 “Spesifikasi cincin karet sambungan air minum, air limbah dan air hujan”. Key word : Rubber Seal, joint rings, water supply ABSTRAK Penelitian ini bertujuan untuk mempelajari jumlah penggunaan campuran karet RSS/SBR dan Carbon Black pada pembuatan kompon cincin karet perapat air minum. Rasio RSS/SBR adalah (35/65, 25/75, 15/85) phr dengan carbon black 20 phr, 30 phr dan 40 phr. Vulkanisat karet perapat air bersih yang dihasilkan kemudian diuji sifat fisisnya. Secara keseluruhan hasil uji vulkanisat karet perapat air minum hasil penelitian memenuhi SNI 06-4828-1998 dan mempunyai sifat fisik lebih baik dibandingkan sifat fisik sampel dari pasaran. Sifat kekerasan pada penggunaan carbon black yang tetap RSS/SBR yang bervariasi tidak memberikan pengaruh yang berarti, baik sebelum aging dan perubahan setelah aging. Kekerasan yang terbaik dicapai pada jumlah carbon black 30 dan 40 phr dengan rasion RSS/SBR 25/75 yaitu 61 shore A dan 65 shore A serta perubahan 0%. Nilai kuat tarik optimal dicapai pada penggunaan carbon black 20 phr dengan rasio RSS/SBR 22/75 yaitu sebesar 11,38 Mpa dan 12,63 Mpa dengan perubahan sesudah aging -6,31% dan -11,3%. Hasil perpanjangan putus terbaik dicapai pada penggunaan carbon black 20 ogr dengan rasio RSS/SBR 25/75 yaitu 440% dengan perubahan sesudah aging -1,35% serta rasio RSS/SBR 35/65 dengan jumlah carbon black 30 phr sebesar 453% dengan perubahan sudah aging -1,45% . Nilai pampat tetap terbaik dicapai pada penggunaan carbon black 30 phr dan 40 phr serta rasio RSS/SBR 15/85 yaitu 5,39% dan 5,68%. Pembengkahan optimal dicapai pada penggunaan carbo black 40 phr dan rasio RSS/SBR 15/85 yaitu 2,35%. Dari beberapa hasil uji fisik vulkanisat yang menunjukkan nilai terbaik tersebut dipilih karet perapat air minum dengan kompoisisi carbon black 30 phr dari rasio RSS/SBR 25/75 sebagai komposisi yang tepat yang dapat memberikan sifat fisik terbaik dan memenuhi syarat mutu SNI 06/4828-1998 “Spesifikasi cincin karet sambungan air minum, air limbah dan air hujan”. Kata kunci: Seal karet, cincin perapat, air minum.